Orquídeas da Serra de Maranguape: estudo em uma área de elevada riqueza de epífitas em um brejo de altitude nordestino - Gomes, Manuella Maciel (2024)
Ceará typically has a semi-arid climate and deciduous caatinga vegetation. However, there are areas within the state with higher altitude and orographic rainfall that support humid evergreen forest vegetation, known as 'altitude swamps'. These areas are exceptional environments within the Caatinga Domain, enabling species from both the Atlantic and Amazon Rainforests to thrive in the high-altitude swamps surrounded by much drier caatinga environments. One notable example is the Serra de Maranguape, situated between the municipalities of Maranguape and Caucaia in the metropolitan region of Fortaleza, the capital of the state of Ceará. The study confidently conducted a floristic inventory of the Orchidaceae family species in a highland marsh with diverse flora from humid domains. The results provide valuable information on the prevalent life forms in this ecosystem. The study acknowledges the importance of preserving such diverse ecosystems and encourages further research in this area. The inventory was carried out through expeditions on foot along pre-existing trails. During our expeditions, we conducted careful in situ observations of populations and collected reproductive-stage specimens using the walking method. These specimens were then indexed in the collection of the Prisco Bezerra Herbarium at the Federal University of Ceará. We believe that these findings will contribute significantly to the field of orchid research. In addition, we consulted collections of herborized plants and Orchidaceae specialists for information. Our survey confidently revealed the presence of 23 species, which we grouped into 19 genera. Notably, the genus Epidendrum stands out as the most diverse, with three species: E. ramosum, E. rigidum, and E. secundum. The Orchidaceae family in the Serra de Maranguape exhibits a remarkable diversity, with a prevalence of species found in other humid phytogeographic domains such as the Amazon and Atlantic Forest, as well as those found in drier phytogeographic domains like the Caatinga and Cerrado. These findings underscore the urgent need for increased efforts to effectively preserve the study area.